Helicobacter pylori independent chronological change in gastric acid secretion in the Japanese. Issue 4 (1st October 1997) - Kinoshita, Y; Kawanami, C; Kishi, K; Nakata, H; Seino, Y; Chiba, T
Abstract : Background —Gastric acid secretion in Japanese subjects decreases with aging. One of the possible causative mechanisms of this attenuated acid secretion is speculated to be a Helicobacter pylori induced chronic gastritis. The infection rate of this microorganism has decreased recently in Japan. Aims —To investigate whether gastric acid secretion has altered over the past 20 years, and if so, what the influence of H pylori infection might be in the Japanese population. Subjects and methods —Gastric acid secretion, serum gastrin and pepsinogen I and II concentrations, and H pylori infection were determined in 110 Japanese subjects in both the 1970s and 1990s. Results —Basal acid output as well as maximal acid output have greatly increased over the past 20 years, not only in individuals with H pylori infection but also in those without infection. Furthermore, subjects with H pylori infection tended to show decreased gastric acid secretion in comparison with those without infection, particularly in geriatric subjects. There was a positive correlation between gastric acid secretion and serum pepsinogen I concentrations. Conclusions —In Japan, both basal and stimulated gastric acid secretion have increased over the past 20 years; some unknown factors other than the decrease in H pylori infection may play an important role in this phenomenon.